Comparative characteristics of consonants č (ч ), š (ш), h (x) in Kazakh, Turkish and Uzbek languages (Eurasian Journal of Philology Science and Education, 2018)
It is known that each of the modern Turkic languages were formed as the result of a long process of structural development, testing and continuous improvement of the literary (written-spelling, speech, etc.) standards. In this process, perhaps, one of the main factors affecting the development of language, its own rules and combatant elements is chosen and worked out their phonetic system. Phonetic structure of any language consists of consistent and coordinated closely connected in the phonetic and phonological phenomena, which are becoming a steady, stable rules and patterns of the language. Exactly these rules stabilized phonetic laws form the phonetic-phonological structure of a particular language governing the further development and defining its specific characteristics. A comparison of these characteristics between themselves and their comparison with proto-language condition gives a picture of the evolution of these phenomena and show logical shifts in one direction or another.